GAME-BASED SOCCER TRAINING MODELS FOR CHILDREN AGED 6-8 YEARS - M. Alvin Conra; Nofi Marlina Siregar; Yasep Setiakarnawijaya (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2021)
The purpose of this study was to produce and develop a game-based soccer training model for children aged 6 - 8 years and to test its effect on improving children's basic abilities. This study uses the Research and Development (R&D) method from Borg and Gall with 10 stages; 1) research and information; 2) planning; 3) developing superior product forms; 4) preliminary field testing; 5) major product revisions; 6) main field testing; 7) operational product revisions; 8) operational field testing; 9) final product revision, and 10) dissemination and implementation. The subjects in the small group trial were 12 students of SSB Ina Football Soccer School Ciganjur, South Jakarta, and the subjects in the large group trial were 30 students, each consisting of 15 students of SSB Garuda Muda Batipuah, Tanah Datar, and 15 students of SSB Padang Laweh, Agam. . Whereas in the effective test using the subject as many as 30 students of SSB PS Marapi Batu Palano. The strength test of the game-based football training model for children aged 6 - 8 years using a basic motion test instrument, namely TGMD-2, consists of locomotor and manipulative basic motion tests. Data analysis obtained the mean value of the initial test 19.8 for basic locomotor motion and 7.4 for manipulative, and the final test mean value 34.9 for locomotor basic motion and 10.93 for manipulative. The significance test gets a t-count value of 26.87 for locomotor and 12.89 for manipulative, where each is greater than the t-table value of 1.699 at the 0.05 level so it can be denied that the game-based soccer training model has a positive impact and significant to the improvement of the locomotor and manipulative basic development of children aged 6 - 8 years. So that the conclusion that there are 33 game-based football training models is effective and significant for improving the basic motion of children aged 6 - 8 years and the training model is feasible to use and disseminate.